2011
DOI: 10.1007/s11240-011-9988-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inhibitor(s) of β-glucuronidase enzyme activity in GUS-transgenic wheat

Abstract: The uidA gene, encoding for b-glucuronidase (GUS), is the most frequently used reporter gene in plants.As a reporter enzyme, GUS can be assayed both qualitatively and quantitatively. In wheat, there are numerous reports of failure in detecting GUS enzyme activity in tissues of transgenic plants, while other reports have suggested presence of b-glucuronidase inhibitor(s) in wheat tissues. In the present study, we show that the b-glucuronidase enzyme activity is not only tissue-specific but also genotype-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…This probably indicated that the cells with transformation competency could not regenerate after co-cultivation or that gus gene expression was either lost, silenced or inhibited in regenerated plantlets. A similar failure in detecting GUS activity in tissues of transgenic wheat was reported (Ramadan et al 2011), which could result from the presence of some potential GUS enzyme inhibitors in those tissues (Bahieldin et al 2005;Ramadan et al 2011). Kumar et al (2011) found that the CaMV 35S promoter was ineffective in early stages of transgenic plant development in sorghum.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This probably indicated that the cells with transformation competency could not regenerate after co-cultivation or that gus gene expression was either lost, silenced or inhibited in regenerated plantlets. A similar failure in detecting GUS activity in tissues of transgenic wheat was reported (Ramadan et al 2011), which could result from the presence of some potential GUS enzyme inhibitors in those tissues (Bahieldin et al 2005;Ramadan et al 2011). Kumar et al (2011) found that the CaMV 35S promoter was ineffective in early stages of transgenic plant development in sorghum.…”
Section: Discussionsupporting
confidence: 55%
“…Nontransgenic controls never showed blue staining, while sometimes GUS expression and staining can be lacking despite the fact that T-DNA has been integrated (Ramadan et al 2011;Kumar et al 2011). In the first transformants obtained with this protocol PCR showed the presence of gus gene sequences in totally blue-stained lily plants.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that the low GUS activity in root extracts of hydroponically grown plants is largely responsible for this discrepancy in GUS performance between substrates. Low GUS activity, which has often been reported in transgenic wheat harboring the uidA gene, is attributed to non-proteinaceous inhibitors of the β-glucuronidase that are released once cell membranes are disrupted (Bahieldin et al 2005, Ramadan et al 2011. Therefore, it was hypothesized that inhibitors of this enzyme were synthesized preferentially in hydroponically grown plants, which resulted in root extracts with very low GUS activity.…”
Section: Discussionmentioning
confidence: 99%